2022
DOI: 10.3390/microorganisms10081554
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Influence of Different Nucleic Acid Extraction Assays on the Sensitivity of Trypanosoma cruzi-Specific Real-Time PCR

Abstract: For the molecular diagnosis of Chagas disease by real-time PCR (polymerase chain reaction), optimization of diagnostic accuracy is desirable. The detection limit of real-time PCR assays for the diagnosis of Trypanosoma cruzi in human serum is affected by various influences including the choice of the nucleic acid extraction assay. In this study, three nucleic acid extraction assays were compared regarding their influence on the sensitivity of a T. cruzi-specific real-time PCR with 62 reference sera containing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 26 publications
2
7
0
Order By: Relevance
“…A homogenized surveillance system is needed in order to get reliable epidemiological data at a regional level. We also point out that PCR for T. cruzi was provided by the protocol, together with an hemoscopic exam for parasitological direct diagnosis; however, molecular methods are not standardized for the diagnosis of Chagas disease and only a few reports evaluated the performance of commercial methods [ 57 , 58 ]. In order to promote the use of these high-sensitivity tests, they should be standardized and there should be a consensus by the scientific community on their use [ 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…A homogenized surveillance system is needed in order to get reliable epidemiological data at a regional level. We also point out that PCR for T. cruzi was provided by the protocol, together with an hemoscopic exam for parasitological direct diagnosis; however, molecular methods are not standardized for the diagnosis of Chagas disease and only a few reports evaluated the performance of commercial methods [ 57 , 58 ]. In order to promote the use of these high-sensitivity tests, they should be standardized and there should be a consensus by the scientific community on their use [ 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…DNA extraction and real-time PCR were performed as described previously by Kann et al (2022) [ 20 ]. In short, extractions were made from serum following the manufacturers’ protocols of the RTP Pathogen Kit (Invitek Molecular GmbH, Berlin, Germany) with the samples from study part I and of the MagaBio Plus Virus DNA/RNA purification kit version 2 (Hangzhou Bioer Technology Co., Ltd., Hangzhou, China) for the samples from study part II.…”
Section: Methodsmentioning
confidence: 99%
“…In short, extractions were made from serum following the manufacturers’ protocols of the RTP Pathogen Kit (Invitek Molecular GmbH, Berlin, Germany) with the samples from study part I and of the MagaBio Plus Virus DNA/RNA purification kit version 2 (Hangzhou Bioer Technology Co., Ltd., Hangzhou, China) for the samples from study part II. The extraction and elution volumes were in a similar range over the compared extractions schemes with 200 µL and 60 µL for the RTP assay and 300 µL and 80 µL for the MagaBio assay, respectively [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…The extractions were performed in close temporal association to the blood acquisition events in order to avoid bias due to different states of DNA degradation within the samples. In a former assessment, it could be demonstrated that the use of the two different nucleic acid extraction kits did not have any relevant impact on the test results [54].…”
Section: Dna Extractionmentioning
confidence: 99%
“…All samples were assessed in duplicate. Further details on the PCR approach are provided in detail in the evaluation studies [54][55][56] and summarized below. In particular, the oligonucleotides used for the patent-protected NDO-PCR assay targeting kinetoplast minicircle DNA (GenBank accession number U07846.1) are provided in Table 1.…”
Section: T Cruzi-specific Real-time-pcr (Newly Developed One-ndo)mentioning
confidence: 99%